PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK AMPLANG KELOMPOK UKM â€œWANITA MANDIRI SALIKIâ€ DI DESA SALIKI - Irwansyah; Ilham; Hendra (I-Con Media, 2022)
The aim of this thesis is to determine the partial and simultaneous influence of product quality, price and brand image variables on purchasing decision variables for the SME amplang product "Woman Mandiri Saliki". From the 60 research samples, the research results showed that the product quality variable had a positive effect with a value of tcount (6.702) > ttable (2.002) and the resulting significance value was (0.000) < (0.05). Price also has a positive effect with a value of tcount (2.479) > ttable (2.002) with a resulting significance value of 0.016 < 0.05. Likewise for brand image with a value of tcount (2.288) > ttable (2.002) with a significance value of (0.026) < (0.05) meaning that each variable has a partial influence on the decision to purchase the SME amplang product "Woman Mandiri Saliki". The variables product quality, price and brand image also have a simultaneous influence on purchasing decisions for the SME amplang product "Woman Mandiri Saliki" with a value of fcount (22.824) > ftable (2.77) with Sig. (0.000) < (0.05) and the R Square value is (0.526) or 52.6%, this can be interpreted as simultaneously product quality, price and brand image influencing the decision to purchase the UKM amplang product "Woman Mandiri Saliki" while the rest 47.4% is influenced by other variables not used in this research.